Market research applied as educational innovation: an interdisciplinary academic consulting project - Alabau-Tejada, Nuria; Tejero Martos, Verónica (Journal of Management and Business Education, 2025)
Teaching market research requires active methodologies that link theory and practice. This study focuses on a classroom simulation applied to the Market Research I course, aimed at strengthening understanding of qualitative research, specifically in-depth interviews, through an analysis of tourist behavior in Valencia. The objective was for students to explore the factors that determine the choice of tourist booking channels (physical agencies vs. OTAs) and apply field methodologies in a realistic context. The literature review highlights the transformation of the tourism sector and the importance of experiential methodologies and the development of cross-cutting skills in higher education. The methodology consisted of five phases: design of the simulated scenario, instruction on qualitative techniques, fieldwork, data analysis with specialized software, and presentation of results. The results showed improvements in the understanding of qualitative research, motivation, critical thinking, communication, and professional ethics. The discussion highlights that classroom simulation allows for the consolidation of practical skills and the transfer of theoretical knowledge to real contexts, promoting deep and applied learning in university students.